A Lacanian Reading of Finnegans Wake in Relation to James Joyce's Feminine Structure - Massiha, Laleh (2011)
According to Jacques Lacan, James Joyce was a rare man who could achieve a jouissance normally only accessible to women. The purpose of this study is to ascertain how a male author can obtain this jouissance, by identifying Joyce‘s sexual structure according to Lacan‘s definition of sexuation. Using late Lacanian concepts, this thesis will examine Joyce‘s Finnegans Wake (1939), along with his biography and letters, to find clues as to the sexual structure of the author. Since the paternal function determines the sexual structure of the subject, the function of phallic authority is explored in this thesis through Joyce‘s real father, John Joyce, the imaginary father, in the form of H.C.E from Finnegans Wake, and the role of the symbolic father, played by institutions such as the church. John Joyce‘s inability to perform his patriarchal responsibilities is mirrored in H.C.E, while Joyce himself rejects the influence of the church. I contend that Joyce‘s ‗father foreclosure‘, due to the absence of a strong paternal figure, and his refusal of the Law, results in the feminine structure of his mind and his feminine jouissance, which enables him to write Finnegans Wake. According to Lacan, it is the feminine qualities of the mind such as Infinity, a Phallus-less nature and the Real that makes biological women ‗mad‘; however, these qualities function differently in Joyce, who selects this sexual position knowingly, resulting in genius rather than psychosis. This thesis also holds that the reason for the consciously obscure language of Finnegans Wake is due to Joyce‘s feminine structure, which enables him to create an extremely subjective writing style that has defeated all efforts to analyse it. Key words: Real, Symbolic, Other, Jouissance, Feminine/Real jouissance, Le Sinthome.